No B.S. Marketing to the Affluent - Kennedy, Dan (Ascent Audio, 2019)
In this new edition of No B.S. Marketing to the Affluent, millionaire maker Dan S. Kennedy shows you how to re-position your business, practice, or sales career to attract customers or clients for whom price is not a determining factor. Learn how to sell to those who will always be spending as Kennedy shines the spotlight on the practical strategies used by The Ritz-Carlton, Disney, Harrah's Entertainment, Dove, AARP, Dr. Oz, Starbucks, Williams-Sonoma, DeBeers, the health and wellness industry, and many other fascinating and diverse true-life examples. You'll also discover how to: - Use ten surprising emotional buy triggers the affluent find irresistible - Stop selling products and services and learn how selling aspirations and emotional fulfillment is more profitable - Use Kennedy's Million-Dollar Marketing System. A step-by-step blueprint comparable to those developed for six-figure clients, ready for do-it-yourself use - Apply the magic language of "membership" to any business for the affluent . . . from pizza shops and medical practices to retail stores and pet hotels.